ANALISIS PERMODALAN DAN RENTABILITAS PADA KELOMPOK BANK BERDASARKAN MODAL INTI (KBMI) IV - Aprillia Zhulaika (2023)
This writing aims to determine the impact of capital (CAR) on profitability (ROA) in Bank Groups Based on Core Capital IV. The writing method used is descriptive analysis of data using Microsoft Excel. Methods of data collection through library research and documentation studies, using secondary data sources obtained through the Annual Report and Publication Report of each bank. Based on the results of the analysis conducted, it shows that there are conditions where the value of the Capital Adequacy Ratio (CAR) ratio has an impact on the Return On Assets (ROA) value, seen from when the CAR ratio rises, followed by an increase in ROA, and vice versa. This condition is compatible with the existing theory. However, in several periods there were CAR ratios that were not related or had no impact on the ROA ratio, meaning that they were not in accordance with existing theory. Keywords: Capital, CAR, Profitability, ROA